Efektivitas Penerapan Electronic Government Pembuatan Kartu Keluarga di Dinas Kependudukan dan Pencatatan Sipil Pada Era Covid-19 di Kabupaten Berau - Dewi Angraini; Masjaya; Rita Kalalinggi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The results of this study indicate that the effectiveness of online services as a form of implementing electronic government for making family cards at the Department of Population and Civil Registration in the Covid-19 Era in Berau Regency is classified as effective and can be carried out quite well in society, there are aspects of achieving goals, integration and adaptation making the measurement of its effectiveness included in a good achievement to be called effective where convenience for the community as a goal has gone according to the wishes to be achieved, as well as the aspect of integration where the socialization process has gone quite well even though it has not been evenly distributed and there are still obstacles, next namely the aspect of adaptation that can be known by both the apparatus and the community have tried their best to adapt to changes in services at the Office of Population and Civil Registration of the Berau Regency, the last is the obstacle factor experienced so that they will always try to improve and find a solution so that the implementation of electronic government .political marketing lies in the minimal and limited funds used in a series of political marketing processes.